Contribution to the chemoreception capacity of juvenile Loggerhead sea turtles (Caretta caretta, L.) - Moreira, Cláudia Sofia Pombo da Fonseca (2010)
Loggerhead sea turtle juveniles (Caretta caretta), pelagic stage, are found in waters of Madeira archipelago. Pelagic turtles are in the main growth phase of their life cycle and consequently higher energy needs. However, knowledge about the ecology of pelagic loggerhead sea turtles is still quite rudimentary, mainly about the mechanisms that lead them to find food in the vast ocean. Studies with other pelagic species, such as procellariiform birds, revealed that the olfactory system play an important role for the detection of feeding areas, through the detection of concentration peaks of DMS (dimethylsulfide), a scent compound that naturally exists in the marine environment and it is related to areas of high productivity. Based on the assumption that loggerhead sea turtles use a similar mechanism, behavioural experiments were conducted in order to analyze the chemoreception capacity to DMS (airborne chemoreception - theoretically responsible for the long distance detection of areas with food patches; and aquatic chemoreception - theoretically responsible for the short distance detection of preys). The first step was to observe if pelagic loggerheads demonstrate sensitivity to DMS and the second was to verify if they really use the DMS, in natural conditions, as an airborne cue to find areas where food patches might be available. Four juveniles of loggerhead sea turtles were tested in captivity and three wild turtles in the open ocean. The results of airborne chemoreception experiments in captivity revealed that one turtle clearly demonstrated sensitivity to DMS and the sea experiments confirmed this result. However, the experiments were not conclusive on the question whether the pelagic turtles actually use the DMS as an airborne cue to detect long distance food patches. In aquatic chemoreception experiments was not observed sensitivity to DMS by the three sea turtles tested. In the classical conditioning experiment, where DMS and food were given nearly at the same time revealed that after a certain period of time, the sea turtle tested did not associated the DMS stimulus with a possible food reward. The main cause of mortality of loggerhead sea turtles in Madeira waters is due to the accidental capture (bycatch) by deep pelagic longlines fishery which the target species is the black-scabbard (Aphanopus carbo) fish. Chub mackerel (Scomber japonicus) is one of the baits used in this fishery. Aquatic chemoreception experiments were conducted in order to evaluate the attractiveness of the chub mackerel for sea turtles. For the three sea turtles tested, the results showed that in 90% of the cases the sea turtles were extremely attracted by the underwater smell of this fish.